Combined analysis of finite element model and audiometry provides insights into the pathogenesis of conductive hearing loss - Hirabayashi, Motoki; Kurihara, Sho; Ito, Ryuya; Kurashina, Yuta; Motegi, Masaomi; Okano, Hirotaka James; Yamamoto, Yutaka; Kojima, Hiromi; Asakura, Takumi (Frontiers in Bioengineering and Biotechnology, 2022)
The middle ear transmits sound to the inner ear via vibrations in the eardrum and ossicles, and damage to the middle ear results in conductive hearing loss. Although conductive hearing loss can be corrected by surgery, the currently available clinical investigations cannot always diagnose the ossicular chain pathology underlying the conductive hearing loss, and even intraoperative findings can be equivocal. Acoustic analysis using finite element models (FEMs) can simulate the sound pressure change at an arbitrary site for each frequency. FEMs are used in acoustic engineering to simulate the frequency-dependent sound pressure distribution at discrete cells in a simulated model and analyze the effects of specific parameters on the audiogram. However, few reports have compared the numerical results obtained using FEMs with data from clinical cases. We used FEMs to simulate audiograms of the air-bone gap (ABG) for various ossicular chain defects and compared these with preoperative audiograms obtained from 44 patients with a normal tympanic membrane who had otosclerosis, middle ear malformations or traumatic ossicular disruption. The simulated audiograms for otosclerosis and attic fixation of the malleus-incus complex both exhibited an up-slope but could be distinguished from each other based on the ABG at 1000 Hz. The simulated audiogram for incudostapedial joint discontinuity exhibited a peak at around 750 Hz and a down-slope above 1000 Hz. In general, the simulated audiograms for otosclerosis, attic fixation and incudostapedial joint discontinuity were consistent with those obtained from clinical cases. Additional simulations indicated that changes in ossicular mass had relatively small effects on ABG. Furthermore, analyses of combination pathologies suggested that the effects of one defect on ABG were added to those of the other defect. These FEM-based findings provide insights into the pathogenesis of conductive hearing loss due to otosclerosis, middle ear malformations and traumatic injury.